Association of B-Type Natriuretic Peptide Level with Residual Kidney Function in Incident Peritoneal Dialysis Patients. Issue 2 (March 2019) - Kawai, Yasuhiro; Tanaka, Shigeru; Yoshida, Hisako; Hara, Masatoshi; Tsujikawa, Hiroaki; Tsuruya, Kazuhiko; Kitazono, Takanari
Background: Residual kidney function (RKF) is an important factor influencing both technique and patient survival in peritoneal dialysis (PD) patients. B-type natriuretic peptide (BNP) is considered a marker of cardio-renal syndrome. The relationship between BNP and RKF in PD patients remains unclear. Methods: We conducted a prospective study of 89 patients who had started and continued PD for 6 months or more in Kyushu University Hospital between June 2006 and September 2015. Participants were divided into low BNP (≤ 102.1 ng/L) and high BNP (> 102.1 ng/L) groups according to median plasma BNP level at PD initiation. The primary outcome was RKF loss, defined as 24-hour urine volume less than 100 mL. We estimated the association between BNP and RKF loss using a Kaplan-Meier method and Cox proportional hazards model and compared the rate of RKF decline between the 2 groups. To evaluate the consistency of the association, we performed subgroup analysis stratified by baseline characteristics. Results: During the median follow-up of 30 months, 30 patients lost RKF. Participants in the high BNP group had a 5.87-fold increased risk for RKF loss compared with the low BNP group after adjustment for clinical and cardiac parameters. A high plasma BNP level was more clearly associated with RKF loss in younger participants compared with older participants in subgroup analysis. Conclusions: B-type natriuretic peptide may be a useful risk marker for RKF loss in PD patients. The clinical importance of plasma BNP level as a marker of RKF loss might be affected by age.